TESTING corticosteroids in IgA nephropathy: a continuing challenge - Tam,FWK; Pusey,CD (Clinical Journal of the American Society of Nephrology, 2017)
IgA nephropathy (IgAN) is the commonest type of glomerulonephritis worldwide, although the prevalence in some countries may be underestimated depending on the local policy for kidney biopsy. Patients with IgAN have a wide range of prognosis, from microscopic haematuria with stable kidney function through to kidney failure. Long term data show that 20-40% of patients progress to end stage kidney disease within 10-20 years of diagnosis. Recurrence of IgA deposition in the transplanted kidney is common, despite patients being on immunosuppression, and is an important cause of graft failure (1). Clinical features, including hypertension and proteinuria, have been shown to be useful in assessing prognosis. Recently, a combination of histopathological score with clinical data has improved prediction of the risk of progression to kidney failure(2). However, the main role of histology in recent trials has been confirmation of the diagnosis of IgAN, and exclusion of patients with other types of glomerulonephritis or severely scarred kidneys.